Familial associations for rheumatoid autoimmune diseases - Thomsen, Hauke; Li, Xinjun; Sundquist, Kristina; Sundquist, Jan; Försti, Asta; Hemminki, Kari (Rheumatology advances in practice, 2020)
OBJECTIVE: Previous studies have shown a familial component in RA and in some other rheumatic autoimmune diseases (RAIDs), but because of the different study designs the risk estimates for familial risks differ extensively. The objective of this study is to identify familial components for RAIDs. METHODS: We collected data on patients diagnosed in Swedish hospitals with RA, AS, PM/DM, SS, SLE and SSc (and scleroderma) and calculated familial standardized incidence ratios (SIRs) for each of these (concordant) and between them (discordant). RESULTS: The combined number of RAID patients in the offspring population (for whom SIRs were calculated) was 71 544, and in the whole population the number was 152 714, accounting for 19.8% of all autoimmune diseases in Sweden. AS showed the highest concordant familial risk of 18.42, followed by SLE (14.04), SS (8.63), SSc (4.50), PM/DM (4.03) and RA (3.03). There was no sex difference in SIRs. Risks for AS and SLE were 80.28 and 19.53 for persons whose parents and siblings were affected. Discordant risks were far lower than concordant risks, but they were significant for RA with all the other five RAIDs, for SLE and SSc with four RAIDs, for AS and SS with three RAIDs and for PM/DM with two RAIDs, attesting to extensive polyautoimmunity between RAIDs. CONCLUSION: The derived familial risks in this nationwide family study on medically diagnosed RAID are compatible with emerging evidence on the polygenic background of these complex diseases. Novel genetic pathways offer new therapeutic targets that alleviate disease onset optimally in high-risk familial patients and others.
Keywords: polyautoimmunity; ankylosing spondylitis; Sjögren’s syndrome; discordant risks; rheumatoid arthritis; lupus